Earnings Surprises, Investor Sentiments and Contrarian Strategies - Zou, Liping; Chen, Ruishan (International Journal of Economics and Financial Issues, 2017)
This study documents that contrarian investment strategies offer superior returns because these strategies exploit investors' expectation errors. There are two sources of expectation errors, naïve extrapolation of past performance and biased analysts' earnings forecasts. Our results suggest that investors naively extrapolate past performance and overestimate the future growth rates of glamour stocks relative to value stocks. In addition, analysts tend to be excessively pessimistic about value stocks and over optimistic about glamour stocks. We find that both positive earnings surprises and negative earnings surprises significantly affect subsequent returns. However, negative earnings surprises have less impact on value stocks relative to glamour stocks. We also find new evidence that investor sentiments could be an alternative source of superior performances from value stocks. Our results indicate that when the investor sentiment is higher, value stocks earn significant higher returns than glamour stocks. Keywords: contrarian strategy, value and glamour stocks, earnings surprise, investor sentiments JEL Classifications: G02, G11, G14